Феномен мейкерства як інноваційна педагогічна стратегія в STEM-освіті - Хоменко, Любов Григорівна; Кашуба, Сергій Володимирович (Педагогічна Академія: наукові записки, 2026)
Анотація: The article presents a theoretical and methodological analysis of the phenomenon of making (maker movement) as an innovative pedagogical strategy within STEM education, highlighting its role in the development of competency-based and activity-oriented approaches to learning. The essence of the term “maker” is defined in the context of modern education, and its didactic potential in developing technological, engineering, and project competencies of learners is examined. Maker practices are considered an effective tool for activating learning, stimulating creative and critical thinking, and fostering problem-solving and project-based skills in interdisciplinary educational contexts.Special attention is given to the practical implementation of the maker approach in the educational process at the Faculty of Poltava V. G. Korolenko National Pedagogical University. The organization of interdisciplinary maker laboratories within the courses “Project Activity in STEM Education” and “Information and Communication Technologies in Education” is described, where students develop prototypes of educational devices, interactive models, and robotic systems using 3D printing, Arduino kits, and sensor platforms. Practical activities have demonstrated an increase in motivation, development of critical thinking, teamwork skills, and the ability to engage in innovative project-based learning.The role of the teacher as a facilitator, mentor, and moderator of educational interaction is emphasized, creating conditions for active learning, independence, and responsibility for project outcomes. This approach ensures the development of creativity, critical thinking, digital literacy, and competencies necessary for interdisciplinary project design. Maker education in STEM integrates theoretical knowledge with practical activities, develops professional competencies of future educators, and contributes to the creation of an innovative learning environment adapted to the needs of a modern digital society.